Design gráfico : análise da relação com a performance da micro e pequena empresa - Nery, Maria Martins Rebolças (2015)
Design has a central role in business, participating in a crucial way in the cultural and economic interchange of society. One of the competences of the graphic design professional is the development of Corporate Visual Identity (CVI). It has the function